The impact of using a cloud supply chain on organizational performance. Issue 1 (27th June 2020) - Lin, Meichun; Lin, Chinho; Chang, Yong-Sheng
Abstract : Purpose: This study aims to indicate the advantages of using cloud computing services, including the ways in which firms use cloud-based services to achieve accessibility, better communication, flexibility and effective provision of services. However, little evidence has been obtained related to the effectiveness of applying cloud computing services to supply management chains. Design/methodology/approach: In this study, a sample of 223 top 1, 000 manufacturing firms in Taiwan that had implemented cloud-based supply chain management systems (CSCMs) was surveyed to determine what kind of internal resources in these companies were allocated to this implementation effort, how collaborative relationships were established in the existing supply chain to help make the transitions successful, how well their systems are working now that they have been implemented and whether these new systems have improved cycle time performance and the overall performance of their organizations. The study also examines the interrelationships among these variables. Findings: The results reveal that, from the perspective of the managers who were surveyed, an effective allocation of internal organizational resources does have a positive, strong effect on external CSCM conditions. They also showed that when the relationship between internal and external resources is well constructed, the result is that CSCM improves supply chain management cycle time performance, which, in turn, leads to positive organizational performance. Originality/value: The study reports some useful insights from the managers of CSCM systems related to how the execution of CSCM solutions can improve cycle time and organizational performance by enhancing internal organizational management and joint collaboration among supply chain partners. The findings from this survey will be useful to managers who are considering creating cloud-based supply management systems in the future.